Utilization of Educational Programmes in Reformation of Prison Inmates in Nigeria - Chidiebele, Ogbaka, Luke; Nnadi, Ewelum, Johnson; Anthony, Apiti (Asian Journal of Education and Training, 2017)
Education is the most powerful instrument for change in behaviour. Reformation of prison inmates can only be achieved through education and training. Prison education is therefore an alternative strategy that would enable the prisoners leave the prison with more skills and be in position to be employed at released. This paper, therefore, discussed some concepts, purpose of prison education, educational programmes for prisoners and then came up with conclusion and recommendations.